Putting humidity in its place. - Bretz, E.A (IEEE spectrum)
Humidity in the air trapped between the outer skin of the plane and the interior bulkheads condenses, then freezes during high-altitude flight, and melts on landing. The water causes malfunctions in electrical systems and corrodes the aircraft fuselage, soaks insulation, and, after enough flights, adds to the plane's load. A Swedish aerospace company, CTT Systems AB (Nykoping), aims to stop the damage at its source by dehumidifying the trapped air. Its Zonal Drying System is in development as an option for the next generation of Boeing 737s. the system uses a desiccant dehumidifier to dry out the area between the passenger cabin and aircraft skin. The water vapor in the air is not allowed to condense, and so never soaks the insulation nor remains from one flight to the next.